Disaster management for the Philippine Supreme Court library - Nicerio, Jessel C. (2010)
The term 'disaster' is quite ambiguous and can cover a wide range of events from minor incidents to grave emergencies. Disaster in the even best-run institutions can and do happen. Thus, preventive measures are very important not only for the affected areas but for every area that a calamity is calculated to hit and to be able to do that, the local people or the people inside each institution need to be educated to such possibility. This study aimed: To find out the kinds of hazards the library and its collections are exposed to in the circumstances where it is now; to discover the kinds of disasters and hazards the library has experienced since its rehabilitation from destruction due to the bombing of Manila during World War II and how it has coped with these incidents (i.e. if it coped adequately according to set standards such as that recommended by IFLA); and to propose the applicable disaster management and recovery program that can best meet the needs of the Library of the Supreme Court of the Philippines.